2014
DOI: 10.2341/12-486-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chlorhexidine and/or Ethanol Treatment on Bond Strength of an Etch-and-rinse Adhesive to Dentin: An In Vitro and In Situ Study

Abstract: Bond strength suffered degradation over time and was not influenced by dentin treatments with chlorhexidine and/or ethanol. Adhesive bond degradation was less affected under in situ conditions than in vitro. SUMMARYThe aim of this study was to evaluate the effect of a chlorhexidine and/or ethanol application on the bond strength of an etch-and-rinse, hydrophobic adhesive system either under in vitro aging or in situ cariogenic challenge. The dentin surface of 36 human third molars were flattened and allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
5
12
0
6
Order By: Relevance
“…In the 24 h subgroup meta-analysis, as in the immediate follow-up group, chlorhexidine application did not influence microtensile bond strength. This is in agreement with the findings of several authors [24][25][26][27][28]30,31].…”
Section: Discussionsupporting
confidence: 94%
“…In the 24 h subgroup meta-analysis, as in the immediate follow-up group, chlorhexidine application did not influence microtensile bond strength. This is in agreement with the findings of several authors [24][25][26][27][28]30,31].…”
Section: Discussionsupporting
confidence: 94%
“…[ 35 ] found that the incorporation of 2% CHX into ethanol-wet bonding preserved bond strength to both sound and caries-affected dentin, and reduced interfacial nanoleakage after 12 months, while the incorporation of 2% CHX to water-wet bonding preserved bond strength only to sound dentin after aging. Nevertheless, Simoes et al .,[ 37 ] who evaluated the effect of CHX and/or ethanol application on the bond strength of an etch-and-rinse, hydrophobic adhesive system under either in vitro aging or in situ cariogenic challenge, showed that CHX, ethanol, or CHX + ethanol did not affect the μTBS after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was showed that use of absolute alcohol resulted in a non-significant decrease in µTBS compared to the control group [22]. Some authors evaluated the effect of ethanol and chlorhexidine (CHX) on the bond strength and reported that both solvents resulted in a non-significant decrease in bond strength after 24 hours, with greater decrease in bond strength with the use of ethanol compared to CHX [23].…”
Section: Discussionmentioning
confidence: 99%